2019
DOI: 10.34128/je.v6i2.108
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Plastik mulai banyak diminati di kalangan masyarakat. Penyebabnya adalah faktor kebutuhan akan penggunaan plastik, serta adanya kemajuan teknologi manufaktur dari material itu sendiri. Dalam hal ini industri plastik harus terus meningkatkan produksinya baik dalam hal kualitas maupun kuantitas. Untuk menghasilkan produk plastik yang berkualitas ada beberapa mesin yang digunakan. Pada penelitian ini mesin yang digunakan adalah mesin blow molding BM 01, yang bertujuan untuk menghasilkan produk botol 215 ml. Selai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…Property in 17 days means the property is simpler as property ownership of a person or group of people usually in the form of land and buildings that stand on it, as well as facilities and infrastructure that are part of the building. Based on the definit ion above, where there is an emphasis on the word property and ownership, it can be concluded that property is the right to own a plot of land and use whatever is in it 5 .…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Property in 17 days means the property is simpler as property ownership of a person or group of people usually in the form of land and buildings that stand on it, as well as facilities and infrastructure that are part of the building. Based on the definit ion above, where there is an emphasis on the word property and ownership, it can be concluded that property is the right to own a plot of land and use whatever is in it 5 .…”
Section: Literature Reviewmentioning
confidence: 99%
“…There needs to be a service that can be used to choose homes that are by following the wishes of consumers so that to buy a prospective home buyer does not have to go to any existing housing developer to get information about the desired house. Besides consumers can also compare prices and areas of the house directly using the system of each type of house that exists 5 . A decision support system for the selection of houses, using the AHP (Analytical Hierarchy Process) model can be used as an alternative to assist the decision-making process.…”
Section: Introductionmentioning
confidence: 99%
“…When products are of higher quality and can be offered at lower prices, it elevates the competitiveness of enterprises and industries. Economic factors highlights the need for companies to prioritize and maintain high standards of electrical power quality service to remain competitive in the market [6,7]. The growing demand for electricity has resulted in an increase in the number of sensitive loads that require high-quality power and improved network performance [8].…”
Section: Introductionmentioning
confidence: 99%